PENGARUH FASILITAS KERJA, LINGKUNGAN KERJA DAN GAYA KEPEMIMPINAN TERHADAP PRODUKTIVITAS KARYAWAN PT. PERKEBUNAN NUSANTARA III - Sianipar sianipars; Ir. Deni Faisal Mirza, M.M (JEBIM Prima, 2022)
This study aims to determine whether work facilities, work environment and leadership style affect employee productivity at PT. Perkebunan Nusantara III. The instrument used is a questionnaire to obtain data. The population used is 672 and 85 act as samples. From the data processing obtained Simultaneous Test with Fcount of 7.566>2.71(Ftable) from the above results, it can be indicated that the results of the study H0 are rejected and for H1 are accepted. This is also supported by a significant value of 0.000<0.05. Therefore, the independent or independent variables of work facilities, work environment and leadership style together contribute to the influence of the dependent or independent variable, namely employee productivity. Partial Test is also obtained with the value of tcount from the independent variable or independent of work facilities (-2,194)< ttable(1,988), or the value of the significance of t from the facility variable (0.031)<(0.05), tcount value of the independent or independent variable from the work environment (2.226)>(1.988), or the value of the significance of t from the work environment variable (0.029)<(0.05) and the t-value of the independent variable or independent of leadership style (3.278)>ttable(1.988), or the value of the significance of t of the independent or independent variable of leadership style (0.002)<(0.05).